Membranous glomerulonephritis – a common, unspecific pattern of glomerular injury - Starzyńska-Kubicka, Aleksandra; Perkowska-Ptasińska, Agnieszka; Górnicka, Barbara (Polish Journal of Pathology, 2018)
Membranous nephropathy (MN) is a chronic form of glomerulonephritis, associated with the presence of immune complexes beneath the podocytes on the subepithelial region of glomerular capillaries. MN is not a disease entity but one of relatively common patterns of glomerular injury that may be a manifestation of primary renal autoimmunological reaction or may evolve as a phenomenon secondary to wide spectrum of systemic processes.